2023
DOI: 10.3390/electronicmat4010004
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Adsorption on TiO2(110)/Water Interface: Nonadiabatic Molecular Dynamics Simulations for Photocatalytic Water Splitting

Abstract: Chloride is one of the most abundant ions in sea water, which is more available than fresh water. Due to lack of H2O adsorbate states near the valence band maximum (VBM) edge, the difficulty of water dissociation incidents has been reported on the rutile TiO2 surface as the excitation energy is around the band gap energy of TiO2. It is interesting whether the extra chloride can be a benefit to the water dissociation or not. In this study, the models of chlorine adatoms placed on the rutile TiO2 (110)/water int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…When the Hubbard U parameter for titanium d-orbitals U Ti(d) = 4.2 eV is incorporated, the resulting optical absorption spectrum shows a red shift compared to neglect of the Hubbard correction. Interestingly, despite these adjustments, our analysis reveals that there is no significant difference in the absorption characteristics between the TiO 2 surfaces with and without the Hubbard correction [23,62,63]. This finding suggests that the Hubbard correction does not markedly alter the absorption properties of these surfaces, at least within the range of our study.…”
Section: Pristine Surfacesmentioning
confidence: 49%
“…When the Hubbard U parameter for titanium d-orbitals U Ti(d) = 4.2 eV is incorporated, the resulting optical absorption spectrum shows a red shift compared to neglect of the Hubbard correction. Interestingly, despite these adjustments, our analysis reveals that there is no significant difference in the absorption characteristics between the TiO 2 surfaces with and without the Hubbard correction [23,62,63]. This finding suggests that the Hubbard correction does not markedly alter the absorption properties of these surfaces, at least within the range of our study.…”
Section: Pristine Surfacesmentioning
confidence: 49%
“…Summarizing this subsection, we observed that the majority of recent studies on doped TiO 2 have found the accuracy of optical property calculations conducted using several DFT-based computational techniques to be satisfactory. However, a few exceptions exist where more advanced techniques such as TDDFT, GW, or BSE methods were also employed [184,185]. These preferences indicate that despite its acknowledged limitations in describing optical properties, DFT still contributes to exploratory research.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Nanocrystalline titanium dioxide (TiO 2 ) has many applications due to its optical, thermal, photocatalytic, and electrophysical properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For instance, nanocrystalline TiO 2 is utilized in dye-sensitized solar cells, hydrogen production and storage processes, sensors, rechargeable batteries, self-cleaning and antibacterial surfaces.…”
Section: The Present Status Of Titanium Dioxide Nanomaterials Researchmentioning
confidence: 99%
“…Currently, the most active research is related to the photocatalytic activity of TiO 2 nanoparticles for the environmental cleanup of organic pollutants. Due to the chemical stability, non-toxicity, and low cost TiO 2 is considered the most promising photocatalytic for the degradation of pollutants in water and in air [1][2][3][4][9][10][11][12]15]. Titanium dioxide has three naturally occurring polymorphs: rutile, anatase with the tetragonal crystal lattice, and brookite with the orthorhombic crystal lattice [16][17][18].…”
Section: The Present Status Of Titanium Dioxide Nanomaterials Researchmentioning
confidence: 99%
See 1 more Smart Citation